2013
DOI: 10.1111/jdv.12305
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis concurrent with inflammatory bowel disease

Abstract: Asian patients having psoriasis concurrent with IBD exhibited different characteristics as compared with those having psoriasis only, particularly in terms of psoriasis severity, risk of psoriatic arthritis, systemic inflammatory parameters and presence of autoimmune comorbidity. However, further studies elucidating the exact pathogenesis and including a larger number of patients are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…As previously mentioned, the role of IL‐10 has already been studied in psoriasis as well as IBD . In addition, many studies have already been published which support the association of psoriasis and IBD . Thus, we wanted to determine the possibility of creating a better psoriasis animal model by combining imiquimod‐induced and IL‐10 deficient mice models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, the role of IL‐10 has already been studied in psoriasis as well as IBD . In addition, many studies have already been published which support the association of psoriasis and IBD . Thus, we wanted to determine the possibility of creating a better psoriasis animal model by combining imiquimod‐induced and IL‐10 deficient mice models.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis of psoriasis and IBD share other common mechanisms, as Th 1 and Th 17 pathways, in addition to IL‐10 . Moreover, previous reports also support the association between psoriasis and IBD . Therefore, a new attempt to use IL‐10 deficient mice in psoriasis animal models seems appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…reported that patients with both psoriasis and IBD tended to have more severe psoriasis and earlier onset, and significantly more PsA and other autoimmune diseases. Another Korean study using the claims database also showed increased prevalence of IBD in the psoriatic population . A meta‐analysis reviewing all ethnic groups also showed a 2.53‐fold increased risk of developing Crohn's disease and a 1.71‐fold increased risk of developing UC …”
Section: Discussionmentioning
confidence: 91%
“…Clinically, PsA may also involve enthesitis, tenosynovitis, and dactylitis [2]. Both psoriasis and PsA may have varying degrees of severity, and in humans they have been associated with comorbidities such as cardiovascular disease, stroke, inflammatory bowel disease, depression, and potentially cancer [5,6].…”
Section: Discussionmentioning
confidence: 99%